Scanning electron microscopy of granuloma annulare - Hiram Larangeira de Almeida Jr; Eduardo de Barros Coelho Bicca; Mariani Magnus de Andrade; Pedro da Rocha Andrade Neto (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Light microscopy of granuloma annulare shows mucin deposition with lympho-histiocytic infiltrate. We describe the ultrastructural three-dimensional aspects of a typical case of granuloma with characteristic histopathological findings. At the ultrastructural level, affected collagen bundles and granular mucin deposition were observed. Round cells corresponding to lymphocytes were identified. Bigger oval cells, corresponding to isolated or palisading histiocytes were also found. The ultrastructural aspects overlap with light microscopy and contribute to its iconographic documentation.